Neurobiology of interval timing - Merchant, Hugo; de Lafuente, Víctor (Advances in experimental medicine and biology, 2014)
The study of how the brain processes temporal information is becoming one of the most important topics in systems, cellular, computational, and cognitive neuroscience, as well as in the physiological bases of music and language. During the last and current decade, interval timing has been intensively studied in humans and animals using increasingly sophisticated methodological approaches. The present book will bring together the latest information gathered from this exciting area of research, putting special emphasis on the neural underpinnings of time processing in behaving human and non-human primates. Thus, Neurobiology of Interval Timing will integrate for the first time the current knowledge of both animal behavior and human cognition of the passage of time in different behavioral context, including the perception and production of time intervals, as well as rhythmic activities, using different experimental and theoretical frameworks. The book will the composed of chapters written by the leading experts in the fields of psychophysics, functional imaging, system neurophysiology, and musicology. This cutting-edge scientific work will integrate the current knowledge of the neurobiology of timing behavior putting in perspective the current hypothesis of how the brain quantifies the passage of time across a wide variety of critical behaviors
Description based upon print version of record